2013
DOI: 10.1007/s00484-013-0664-9
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of diurnal variations in temperature on non-accidental mortality among the elderly population of Montreal, Québec, 1984–2007

Abstract: The association between short-term changes in ambient temperature and daily mortality has been described widely in the literature. A few recent papers support the hypothesis that diurnal variations in temperature may also have an impact on mortality, independent of the effect of daily mean temperature. The objective of the thesis was to determine whether variations in diurnal temperature increased daily non-accidental mortality among the elderly population of Montreal, Quebec, during the 1984-2007 study period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…However, more than half of related previous studies assumed and demonstrated a linear relationship between DTR and mortality with evidence of increasing mortality with increasing DTR in different regions, including cities in China (Cao et al, 2009;Yang et al, 2013;Zhou et al, 2014) and Korea (Lim et al, 2012). In agreement with our findings, an elderly population in Montreal, Canada, showed a non-linear relationship between lag 0-30 days DTR and nonaccidental mortality (Vutcovici et al, 2014). Moreover, Luo et al (2013) found a U-shaped relationship between DTR and daily mortality in Guangzhou, China, claiming a stronger effect of higher and lower DTR than moderate DTR on mortality.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, more than half of related previous studies assumed and demonstrated a linear relationship between DTR and mortality with evidence of increasing mortality with increasing DTR in different regions, including cities in China (Cao et al, 2009;Yang et al, 2013;Zhou et al, 2014) and Korea (Lim et al, 2012). In agreement with our findings, an elderly population in Montreal, Canada, showed a non-linear relationship between lag 0-30 days DTR and nonaccidental mortality (Vutcovici et al, 2014). Moreover, Luo et al (2013) found a U-shaped relationship between DTR and daily mortality in Guangzhou, China, claiming a stronger effect of higher and lower DTR than moderate DTR on mortality.…”
Section: Discussionsupporting
confidence: 93%
“…The effect of DTR on mortality has been studied in low altitude regions with low DTR (Holopainen et al, 2013;Lim et al, 2012;Yang et al, 2013;Zhou et al, 2014), but the effect of high DTR on mortality has been little studied (Luo et al, 2013;Vutcovici et al, 2014). To our knowledge, this is the first attempt to explore the effect of DTR on non-accidental, cardiorespiratory, cardiovascular and respiratory mortality in a high-altitude city in southwest China with a large range in daily temperature.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A study examined DTR effects on elderly mortality in Canada and observed a cumulative 5 and 11 % increase in mortality due to increases in DTR from the 25th to the 75th and the 75th to the 99th percentile, respectively (Vutcovici et al 2013). The study area (Montreal, Canada) experienced relatively greater DTR (up to 28.1°C) than Asian regions (up to 16°C) (Kan et al 2007).…”
Section: Introductionmentioning
confidence: 97%